Service quality affecting student satisfaction in higher education institutions in Ghana - George Kofi Amoako; George Oppong Ampong; Antoinette Yaa Benewaa Gabrah; Felicia de Heer; Alex Antwi-Adjei (Cogent Education, 2023)
AbstractHigher education stakeholders have re-strategized to identify the unique competitive causes of comfortability among students’ satisfaction. Student satisfaction has been largely observed in the literature as a significant strategy and competitive factor for higher education providers. This has compelled institutions to implement quality measures to attract and retain both potential and current students. Therefore, this research is to explore the determinants of student satisfaction. Cross-sectional data was generated from a purposive sample of 400 students across higher education institutions in Ghana. The data was analysed using multiple regression. Expectation theory is the theory that unpins this study. The results reveal that administrative services, academic services, and physical evidence are significant components of service quality. The outcomes of the study show there is a positive and significant relationship between satisfaction, academic services, and administrative services; physical evidence influence student satisfaction.